75 Late-Breaking: Investigation into the relationship Methanobrevibacter millerae YE315. (7th December 2018) - McGovern, E; Kenny, D; Kelly, A; Waters, S
Abstract: The objective of this study was to investigate the similarity of the representative 16S rRNA (Operational taxonomic units) OTUs classed as Methanobrevibacter which were derived from four separate studies from two animal experiments investigating the effect of residual feed intake (RFI) phenotype on rumen microbiota. Archaeal and bacterial libraries were generated targeting the V4 region of the 16S rRNA gene for: Post mortem rumen solid and liquids digesta samples of Simmental bulls divergent for RFI offered a concentrate ad libitum diet during their finishing period. Rumen liquid digesta samples collected from Charolais (CH) and Friesian (HF) steers offered a concentrate ad libitum diet as yearlings, via stomach intubation. Rumen liquid digesta samples collected from CH and HF steers offered a concentrate ad libitum diet at finishing phase via stomach intubation. Post mortem rumen solid, liquid and epimural samples collected from HF and CH steers offered concentrate diet ad libitum at finishing phase. Libraries for each experiment were sequenced on the Illumina MiSeq. Experiments were analysed individually. Sequences were clustered at 97% identity into individual OTUs using RDP classifier (Wang, Garrity et al. 2007). OTUs classified as from the Methanobrevibacter genera from the rumen liquor of analysis 1–4 correlated negatively with RFI (P < 0.05). Sequences were than aligned against the NCBI non-redundant nucleotide database and each other. The closest full genome match to each Methanobrevibacter OTU identified was Methanobrevibacter millerae YE315 (M.YE315) with at least 97% identity. Sequences from each analysis were 97% identical to each other when compared using BLAST. Due to its consistency across breed, age and irrespective of castration, abundance of M.YE315 may be an indicator of host RFI status in animals fed a high concentrate diet.